A Robust Wavelet Based Watermarking System for Color Video - Alireza Ghasemi; Hooshang Kazemi (Majlesi Journal of Electrical Engineering)
In this paper, we propose a wavelet based watermarking system. The system use wavelet transform for red, green and blues channel independently. We use space-time coding for encoding the watermark message before data embedding.  The bit-error-rate of recovered message is calculated.  The embedding factor is selected in such a way that the host video maintains the same peak signal to noise ration with/without using space-time coding.  The developed system is further examined, when host video faces compression and noise addition. Result shows the effectiveness of proposed watermarking system, especially when space-time coding is used.äºå¯é çåºæ¼å°æ³¢è®æçæ¸åæ°´å°ç³»çµ±çå½©è²è¦é »æè¦å¨æ¬æä¸ï¼æåæåºäºä¸ç¨®åºæ¼å°æ³¢è®ææ°´å°ç³»çµ±ãè©²ç³»çµ±ä½¿ç¨å°æ³¢ç¨ç«å°è®æçºç´ï¼ç¶ åèè²ééãæåä½¿ç¨ç©ºæç·¨ç¢¼æ¸æåµå¥ä¹åç·¨ç¢¼è©²æ°´å°ä¿¡æ¯ãæ¢å¾©çæ¶æ¯çèª¤ç¢¼çè¢«è¨ç®ãåµå¥å åä»¥éæ¨£çæ¹å¼ï¼å¨ä¸»æ©è¦é »ä¿æç¸åçå³°å¼ä¿¡èè/åªè²æ¯èä¸ä½¿ç¨ç©ºæç·¨ç¢¼é¸æãæéç¼çç³»çµ±çé²ä¸æ¥ç ç©¶ï¼ç¶ä¸»è¦é »å£ç¸®é¢è¨ååªè²å æ³ãçµæè¡¨ææåºæ°´å°ç³»çµ±çæææ§ï¼ç¹å¥æ¯ç¶ä½¿ç¨ç©ºæç·¨ç¢¼ã